Nexus between capital expenditure and inclusive economic growth during the Covid-19 pandemic - Chandra, Herlina Aria; Badrudin, Rudy (Journal of Business and Information Systems (e-ISSN: 2685-2543), 2024)
Regional economic development can lead to an increase in economic growth, a reduction in unemployment and inequality, and a decrease in poverty levels in the area. However, the COVID-19 pandemic has resulted in a decline in economic activities, causing increasing unemployment and poverty in Indonesia. This study aims to analyze the influence of Regional Original Revenue (ROR) and General Allocation Fund (GAF) on capital expenditure and economic growth, with the COVID-19 pandemic as a moderating variable in all districts and cities throughout Indonesia from 2019 to 2022. The sample consists of 341 districts and cities with complete data on the required variables. The analytical techniques employed include path analysis, descriptive analysis, model fit, and multicollinearity tests. The research findings indicate that ROR and GAF significantly positively affect capital expenditure. Capital expenditure can mediate the relationship between ROR, GAF, and economic growth. However, economic growth cannot mediate the relationship between capital expenditure and unemployment or poverty. Covid-19 is found to negatively moderate the relationship between capital expenditure and unemployment while positively moderating the relationship between capital expenditure and poverty